2018
DOI: 10.1130/g39866.1
|View full text |Cite
|
Sign up to set email alerts
|

Pre–mass extinction decline of latest Permian ammonoids

Abstract: The devastating end-Permian mass extinction is widely considered to have been caused by large-scale and rapid greenhouse gas release by Siberian magmatism. Although the proximate extinction mechanisms are disputed, there is widespread agreement that a major extinction pulse occurred immediately below the biostratigraphically defined Permian-Triassic boundary. Our statistical analyses of stratigraphic confidence intervals do not comply with a single end-Permian extinction pulse of ammonoids in Iran. High turnov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 31 publications
1
12
0
Order By: Relevance
“…A similar substantial pre-MEE decline of radiolarians has been reported in the Upper Permian (late Changhsingian) in South China (Feng et al 2007;Feng and Algeo 2014). Furthermore, a recent statistical analysis of Permian ammonoids revealed that high turnover rates and extinction pulses occurred during the last 700 kyr of the Permian (Kiessling et al 2018). As a first approximation, it seems reasonable to assume that the a b Fig.…”
Section: Discussionsupporting
confidence: 65%
“…A similar substantial pre-MEE decline of radiolarians has been reported in the Upper Permian (late Changhsingian) in South China (Feng et al 2007;Feng and Algeo 2014). Furthermore, a recent statistical analysis of Permian ammonoids revealed that high turnover rates and extinction pulses occurred during the last 700 kyr of the Permian (Kiessling et al 2018). As a first approximation, it seems reasonable to assume that the a b Fig.…”
Section: Discussionsupporting
confidence: 65%
“…Research increasingly reveals that such crises are less abrupt than previously thought. At least two deep-time extinction pulses, associated with wholesale losses of tropical reef systems (the end-Permian and the Toarcian crises) were preceded by community changes, minor extinction pulses and declining body sizes of marine organisms [33][34][35][36]. Improved constraints on the patterns that signal early warning of ecosystem collapse is thus an obvious route to address this question.…”
Section: Addressing Specific Questionsmentioning
confidence: 99%
“…Studies on variations in body size related to extinction episodes usually have focused on the aftermath of a crisis (e.g., Lockwood 2005; Morten and Twitchett 2009; Huang et al 2010). Yet few studies have focused on changes in body size during precrisis times (e.g., He et al 2007, 2010; Zhang et al 2016; García Joral et al 2018; Kiessling et al 2018).…”
Section: Introductionmentioning
confidence: 99%